Phenolics, Antioxidant and Antibacterial Activities of Immature and Mature Blumea balsamifera Leaf Extracts Eluted with Different Solvents - Sirinapha Jirakitticharoen; Wudtichai Wisuitiprot; Pongphen Jitareerat; Chalermchai Wongs-Aree (Journal of Tropical Medicine)
Blumea balsamifera (L.) DC., belonging to the Asteraceae family, also known as “ngai camphor,” is one of the traditional herbs used in Thailand for folk medicine and a component in local food and drinks. There was, however, no evidence indicating the presence of beneficial compounds at different leaf ages. Exploring various extraction solvents, we investigated the phenolics, flavonoids in particular quercetin content, antioxidant capacity, and antibacterial activity of immature and mature leaf extracts. The dried leaves were macerated in 50% ethanol, 95% ethanol, hexane, or decocted in water. Bioactive substances were analyzed by UV spectrophotometry and HPLC. Analysis of antioxidant capacity was done byDPPH, ABTS, FRAP, and NO scavenging assays. The antibacterial activity of immature leaf extract eluted with 50% ethanol was subsequentially evaluated in vitro. Extraction with 50% ethanol proved optimal, yielding 1.2–1.6-fold and 1.5-fold greater immature and mature leaf extracts than other solvents. More phenolics (1.2-fold), flavonoids (1.1-fold), quercetin content (4.8-fold), and antioxidant activity (1.3-fold) were found in the immature leaf extract. There was a significant positive correlation between antioxidant activity and bioactive compounds. The immature leaf extract eluted with 50% ethanol showed antibacterial activity against Staphylococcus aureus, with a minimum inhibitory concentration of 0.5 mg/mL. The immature leaves of B. balsamifera are a rich source of quercetin and phenolics, and 50% ethanol proved optimal for extracting bioactive components from these leaves.